Antibiotic contamination and occurrence of antibiotic-resistant bacteria in aquatic environments of northern Vietnam - Hoa, Phan Thi Phuong; Managaki, Satoshi; Nakada, Norihide; Takada, Hideshige; Shimizu, Akiko; Anh, Duong Hong; Viet, Pham Hung; Suzuki, Satoru (The Science of the total environment, 2011)
The ubiquitous application and release of antibiotics to the environment can result in bacterial antibiotic resistance, which in turn can be a serious risk to humans and other animals. Southeast Asian countries commonly apply an integrated recycling farm system called VAC (Vegetable, Aquaculture and Caged animal). In the VAC environment, antibiotics are released from animal and human origins, which would cause antibiotic-resistant bacteria (ARB). This study evaluated occurrence of ARB in the VAC environment in northern Vietnam, with quantitative analysis of antibiotic pollution. We found that sulfonamides were commonly detected at all sites. In dry season, while sulfamethazine was a major contaminant in pig farm pond (475–6662 ng/l) and less common in city canal and aquaculture sites, sulfamethoxazole was a major one in city canal (612–4330 ng/l). Erythromycin (154–2246 ng/l) and clarithromycin (2.8–778 ng/ml) were the common macrolides in city canal, but very low concentrations in pig farm pond and aquaculture sites. High frequencies of sulfamethoxazole-resistant bacteria (2.14–94.44%) were found whereas the occurrence rates of erythromycin-resistant bacteria were lower (< 0.01–38.8%). A positive correlation was found between sulfamethoxazole concentration and occurrence of sulfamethoxazole-resistant bacteria in dry season. The sulfamethoxazole-resistant isolates were found to belong to 25 genera. Acinetobacter and Aeromonas were the major genera. Twenty three of 25 genera contained sul genes. This study showed specific contamination patterns in city and VAC environments and concluded that ARB occurred not only within contaminated sites but also those less contaminated. Various species can obtain resistance in VAC environment, which would be reservoir of drug resistance genes. Occurrence of ARB is suggested to relate with rainfall condition and horizontal gene transfer in diverse microbial community.